Computer aided engineering of an automobile gasoline refueling system - Dake, Mangesh, author; Windom, Bret C., advisor; Marchese, Anthony J., committee member; Venayagamoorthy, Karan S., committee member (Colorado State University. Libraries, 2018)
A vehicle's refueling system, including components which make up the Onboard Refueling Vapor Recovery (ORVR) system, must be designed to meet federally set evaporative hydrocarbon emission regulations and other performance issues inherent to the refueling process, such as premature click-off of the refueling nozzle and spit-back. A Computational Fluid Dynamics (CFD) model able to predict the performance of a vehicle's refueling system could be a valuable tool towards the development of future gasoline refueling system designs, saving the Original Equipment Manufacturer's time and money currently invested in the research and development of these systems. To create an adequate model required for Computer Aided Engineering (CAE) of a modern refueling system, it is paramount to accurately predict the fluid dynamics through and out of a gasoline refueling nozzle, within the different components inside the refueling system, and the outlets of the fuel tank. Using CFD, this study aims to predict the performance of a refueling system. The commercial CFD software, Star-CCM+, was used to model fuel flow through a currently in production refueling system geometry. Experiments were conducted using a test setup to mimic the simulated refueling system to carefully describe the system's boundary and initial conditions and to evaluate the CFD results. It was found that modeling of the fluid dynamics through the air entrainment and pressure port geometries within the refueling nozzle were needed to accurately capture fuel spray behavior as demonstrated by experiments. By monitoring the amount of liquid fuel contacting the pressure port on the refueling nozzle, the simulations are able to identify fillerpipe designs that fail as a result of early click-off. Simulations of the complete refueling system, while neglecting phase change of the fuel, were able to predict the trends and dynamics of the tank pressure experienced by the experiments for varying fuel pump flow rates. The study acts as a guide for future refueling simulations involving fuel evaporation, for which initial results are presented.
Keywords: early click-off; multiphase CFD; refueling system; fuel tank; CFD; refueling nozzle